2023
DOI: 10.3390/d15020234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Pomace Intake on the Rumen Bacterial Community of Sheep

Abstract: The performance of ruminants is affected mainly by the rumen bacterial community. The composition and properties of the rumen bacterial community depend largely on the diet components that are fed to the ruminant. The aim of this study was to determine the effect of grape pomace intake on the rumen bacterial community of sheep. Four different diets, two of which contained dried grape pomace (DGP), were used in this study. Rumen fluid samples from 12 wethers were used for 16S rRNA gene sequencing and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…The alpha diversity of rumen bacteria decreased, while there were marked changes in the bacterial community structure with the consumption of GP. These results differed from those of Rolinec et al (2023) who reported that the consumption of a diet with 1 and 2% GP increased alpha diversity among rumen bacteria and stimulated higher levels of methanogen abundance. The difference among studies may be attributed to differing levels of dietary GP.…”
Section: Discussioncontrasting
confidence: 99%
“…The alpha diversity of rumen bacteria decreased, while there were marked changes in the bacterial community structure with the consumption of GP. These results differed from those of Rolinec et al (2023) who reported that the consumption of a diet with 1 and 2% GP increased alpha diversity among rumen bacteria and stimulated higher levels of methanogen abundance. The difference among studies may be attributed to differing levels of dietary GP.…”
Section: Discussioncontrasting
confidence: 99%
“…There are many feed additives applied in the diet of animals such as probiotics, prebiotics, synbiotics, phytobiotics and food industry waste which have a positive impact on the health condition of farm animals (Gálik et al, 2023;Rolinec et al, 2023;Hanušovský et al, 2020). For example, lactic acid bacteria are used for silage fermentation, other microorganisms can be used as a source of proteins or for providing amino acids, vitamins, etc.…”
Section: Introductionmentioning
confidence: 99%